Healing hearts - Eden, Sarah M. (Proper romance., 2019)
"Miriam Bricks arrives in Savage Wells thinking she is accepting a job as a nurse. Dr. Gideon MacNamara thinks Miriam is coming to be his wife. Despite the misunderstanding, they learn to work together as a team to help the sick and injured. As their relationship grows into something deeper, Miriam's secrets may take away their dreams"--Provided by publisher.